Anda di halaman 1dari 33

# Basic Mathematics

The Laplacian
R Horan & M Lavelle

## The aim of this package is to provide a short self

assessment programme for students who want to
apply the Laplacian operator.

## c 2005 rhoran@plymouth.ac.uk , mlavelle@plymouth.ac.uk

Copyright
Last Revision Date: April 4, 2005
Version 1.0

Table of Contents
1.
2.
3.
4.
5.

## Introduction (Grad, Div, Curl)

The Laplacian
The Laplacian of a Product of Fields
The Laplacian and Vector Fields
Final Quiz
Solutions to Exercises
Solutions to Quizzes

## The full range of these packages and some instructions,

should they be required, can be obtained from our web
page Mathematics Support Materials.

## 1. Introduction (Grad, Div, Curl)

The vector differential operator , called del or nabla, is defined
in three dimensions to be:

i+
j+
k
=
x
y
z
The result of applying this vector operator to a scalar field is called
the gradient of the scalar field:
f
f
f
gradf (x, y, z) = f (x, y, z) =
i+
j+
k.
x
y
z
(See the package on Gradients and Directional Derivatives.)
The scalar product of this vector operator with a vector field F (x, y, z)
is called the divergence of the vector field:
F1
F2
F3
divF (x, y, z) = F =
+
+
.
x
y
z

## Section 1: Introduction (Grad, Div, Curl)

The vector product of the vector with a vector field F (x, y, z) is the
curl of the vector field. It is written as curl F (x, y, z) = F
F3

y

i

=
x
F

F (x, y, z) = (

F2
F3
F1
F2
F1
)i (

)j + (

)k
z
x
z
x
y

j
k

,
y z
F
F
2

where the last line is a formal representation of the line above. (See
also the package on Divergence and Curl.)
Here are some revision exercises.
Exercise 1. For f = x2 y z and F = xi xyj + z 2 k calculate the
following (click on the green letters for the solutions).
(a)

(b)

(c)

(d)

f F

## Section 2: The Laplacian

2. The Laplacian
The Laplacian operator is defined as:
2 =

2
2
2
+
+
.
x2
y 2
z 2

## The Laplacian is a scalar operator. If it is applied to a scalar field, it

generates a scalar field.
Example 1 The Laplacian of the scalar field f (x, y, z) = xy 2 + z 3 is:
2f
2f
2f
+ 2 + 2
2
x
y
z
2

2
2
(xy 2 + z 3 ) + 2 (xy 2 + z 3 ) + 2 (xy 2 + z 3 )
=
2
x
y
z
2

=
(y + 0) +
(2xy + 0) +
(0 + 3z 2 )
x
y
z
= 0 + 2x + 6z = 2x + 6z

2 f (x, y, z) =

## Exercise 2. Calculate the Laplacian of the following scalar fields:

(click on the green letters for the solutions).

## (a) f (x, y, z) = 3x3 y 2 z 3

(b) f (x, y, z) = xz + y
p
1
(c) f (x, y, z) = x2 + y 2 + z 2 (d) f (x, y, z) = p
2
x + y2 + z2
p
1
where r = x2 + y 2 + z 2 .
n
r
n
(b)
rn+2
n(n + 5)
(d)
rn+2

## Quiz Choose the Laplacian of f (r) =

(a)
(c)

1
rn+2
n(n 1)
rn+2

The equation 2 f = 0 is called Laplaces equation. This is an important equation in science. From the above exercises and quiz we see
1
that f = is a solution of Laplaces equation except at r = 0.
r

## The Laplacian of a scalar field can also be written as follows:

2 f = f
i.e., as the divergence of the gradient of f . To see this consider
f
f
f
f = ( i +
j+
k)
x
y
z
f
f
f
( )+
( )+
( )
=
x x
y y
z z
2f
2f
2f
+
+
= 2 f
=
x2
y 2
z 2
Exercise 3. Find the Laplacian of the scalar fields f whose gradients
f are given below (click on the green letters for the solutions).
x
1
x
(a) f = 2xzi + x2 k
(b) f =
i 2 j 2k
yz
y z
yz
1
1
1
(c) f = ez i + yj + xez k
(d) f = i + j + k
x
y
z

## 3. The Laplacian of a Product of Fields

If a field may be written as a product of two functions, then:
2 (uv) = (2 u)v + u2 v + 2(u) (v)
A proof of this is given at the end of this section.
Example 2 The Laplacian of f (x, y, z) = (x + y + z)(x 2z) may be
directly calculated from the above rule
2 f (x, y, z)

## (2 (x + y + z))(x 2z) + (x + y + z)2 (x 2z)

+2(x + y + z) (x 2z)

## Now 2 (x + y + z) = 0 and 2 (x 2z) = 0 so the first line on the

right hand side vanishes.
To calculate the second line we note that
(x + y + z) (x + y + z)
(x + y + z)
(x+y+z) =
i+
j+
k = i+j+k
x
y
z

## Section 3: The Laplacian of a Product of Fields

and
(x 2z)
(x 2z)
(x 2z)
i+
j+
k = i 2k
x
y
z
and taking their scalar product we obtain
(x 2z) =

2 f (x, y, z)

= 0 + 2(x + y + z) (x 2z)
= 2(i + j + k) (i 2k) = 2(1 + 0 2)
= 2.

## This example may be checked by expanding (x + y + z)(x 2z) and

directly calculating the Laplacian.
Exercise 4. Use this rule to calculate the Laplacian of the scalar
fields given below (click on the green letters for the solutions).
(a) (2x 5y + z)(x 3y + z)
(c)

(y z)(x2 + y 2 + z 2 )

(d)

p
x x2 + y 2 + z 2

10

## Proof that 2 (uv) = (2 u)v + u2 v + 2(u) (v) .

By definition 2 (uv) =

2
2
2
(uv)
+
(uv)
+
(uv) . Consider
x2
y 2
z 2

therefore:
2
(uv) =
x2






v
(uv) =
v+u
x x
x x
x
2
2
u v
u
u v
v
v+
=
+
+u 2
x2
x x x x
x
u v
2u
2v
v
+
2
=
+
u
x2
x x
x2
where the product rule was repeatedly used.
2
2u
u v
2v
(uv) =
v+2
+ u 2 and
2
2
y
y
y y
y
2
2u
u v
2v
(uv) =
v+2
+ u 2 . Adding these results yields the
z 2
z 2
z z
z
desired result.
By symmetry we also have:

11

## 4. The Laplacian and Vector Fields

If the scalar Laplacian operator is applied to a vector field, it acts on
each component in turn and generates a vector field.
Example 3 The Laplacian of F (x, y, z) = 3z 2 i + xyzj + x2 z 2 k is:
2 F (x, y, z) = 2 (3z 2 )i + 2 (xyz)j + 2 (x2 z 2 )k
Calculating the components in turn we find:
2
2
2
2
2
(3z
)
+
(3z
)
+
(3z 2 ) = 0 + 0 + 6 = 6
x2
y 2
z 2
2
2
2
2 (xyz) =
(xyz)
+
(xyz)
+
(xyz) = 0 + 0 + 0 = 0
x2
y 2
z 2
2 2 2
2 2 2
2 2 2
2 (x2 z 2 ) =
(x
(x
(x z ) = 2z 2 + 0 + 2x2
z
)
+
z
)
+
x2
y 2
z 2
So the Laplacian of F is:
2 (3z 2 ) =

## Section 4: The Laplacian and Vector Fields

12

Quiz Select from the answers below the Laplacian of the vector field
F = x3 yi + ln(z)j + ln(xy)k .
x2 + y 2
1
k
(a) 6xyi
(b) 6xyi 2 j
z
x2 y 2


1
1
1
y 2 x2

k
k
(c) 3xi + 2 j
(d) y 3 i + x2 j
2
2
z
x
y
z2
Quiz Choose the Laplacian of F = 3x2 zi sin(y)j + ln(2x3 )k at the
point (1, 2, 1)?
(a)

(b) 6i 3k

(c) 3i 3k

(d) 6i 2 j 6k

Quiz Which of the following choices is the Laplacian of the vector field
F = ln(y)i + z 2 j sin(2x)k at (1, 1, )?
(a) i + 2j

(b) 0

(c) 4j + 4 2 k

(d) i + j + k

## Section 5: Final Quiz

13

5. Final Quiz
Begin Quiz Choose the solutions from the options given.
1. Choose the Laplacian of f (r) = 5x3 y 4 z 2 .
(a) 30xy 4 z 2 + 60x3 y 2 z 2 + 10x3 y 4 (b) 30x + 20y 2 + 10
(c) 30xy 4 z 2 + 75x3 y 2 z 2 + 15x3 y 4 (d) 30xy 4 z 2 + 12x3 y 2 z 2 + 15x3 y 4
2. Choose the Laplacian of f (x, y, z) = ln(r) where r =
(a) 0

(b)

2
r2

(c)

1
2r2

(d)

x2 + y 2 + z 2 .

1
r2

## 3. Select the Laplacian of F = x3 i + 7yj 3 sin(2y)k.

(a) 6xi
(c) 6xi + 3 sin(2y)k
End Quiz Score:

## (b) 6xi + 12 sin(2y)k

(d) 6xi 12 sin(2y)k
Correct

Solutions to Exercises

14

Solutions to Exercises
Exercise 1(a)
To find the gradient
partial derivatives:
f
=
x
f
=
y
f
=
z

## of the scalar field f = x2 y z, we need the

2
(x y z) = 2x21 y = 2xy ,
x
2
(x y z) = x2 y 11 = x2 ,
y
2
(x y z) = 0 z 11 = 1 .
z

## Therefore the gradient of f = x2 y z is

f
f
f
f (x, y, z) =
i+
j+
k
x
y
z
= 2xyi + x2 j k .
Click on the green square to return


Solutions to Exercises

15

Exercise 1(b)
To find the divergence of the vector field F = xi xyj + z 2 k, we
recognise that its components are
F1 = x ,

F2 = xy ,

F3 = z 2 ,

## So the divergence is the scalar expression

F1
F2
F3
F =
+
+
x
y
z

2
=
(x) +
(xy) +
(z )
x
y
z
= x11 x y 11 + 2 z 21
= 1 x + 2z .
Click on the green square to return


Solutions to Exercises

16

Exercise 1(c)
The curl of the vector field F whose components are
F1 = x ,

F2 = xy ,

F3 = z 2 ,

## is given by the vector expression:







F3
F2
F3
F1
F2
F1
F =

j+

k
y
z
x
z
x
y




2
2

=
(z )
(xy) i
(z )
(x) j
y
z
x
z



+
(xy)
(x) k
x
y
= (0 + 0) i (0 0) j + (y 0) k
= yk .
Click on the green square to return

Solutions to Exercises

17

Exercise 1(d)
To subtract the curl of the vector F = xixyj+z 2 k from the gradient
of the scalar field f = x2 y z
f F .
we use the results of Exercise 1a and Exercise 1c, where it was found
that
f = 2xyi + x2 j k and
F = yk .
Therefore the difference of these two vectors is
f F

= 2xyi + x2 j k (y)k
= 2xyi + x2 j (1 y)k .

## Click on the green square to return

Solutions to Exercises

18

Exercise 2(a)
The Laplacian of the scalar field f = 3x3 y 2 z 3 is:
2 f

=
=
=
=

2f
2f
2f
+ 2 + 2
2
x
y
z
2
2
2
3 2 3
3 2 3
(3x
y
z
)
+
(3x
y
z
)
+
(3x3 y 2 z 3 )
x2
y 2
z 2

(9x2 y 2 z 3 ) +
(6x3 yz 3 ) +
(9x3 y 2 z 2 )
x
y
z
18xy 2 z 3 + 6x3 z 3 + 18x3 y 2 z .

## Extracting common factors, the scalar 2 f can also be written as


2 f = 6xz 3y 2 z 2 + x2 z 2 + 3x2 y 2

= 6xz 3y 2 (z 2 + x2 ) + x2 z 2 .
Click on the green square to return


Solutions to Exercises

19

Exercise 2(b)

## The Laplacian of the scalar field f = xz + y = x1/2 z 1/2 + y is:




2  1 1
2  1 1
2  1 1
2z2 + y
2z2 + y
2z2 + y
+
+
x
x
x
2 f =
x2
y 2
z 2




1 ( 1 1) 1

1 1 ( 1 1)
=
x 2
z2 +
(1) +
x2 z 2
x 2
y
z 2




1 1 1
1 1 1
=
x 2z2 + 0 +
x2 z 2
x 2
z 2
1
1 1 ( 1 1) 1
1 1 1
=
( )x 2
z 2 + ( )x 2 z ( 2 1)
2 2
2 2
1 3 1
1 1 3
= x 2 z 2 x 2 z 2 .
4
4
This result may be rewritten as



1
1 1 1 2
1
1
2
2
=
f = x2 z 2 x + z
xz
+ 2 .
4
4
x2
z
Click on the green square to return

Solutions to Exercises

20

p
Exercise 2(c) To calculate 2 x2 + y 2 + z 2 , define u = x2 +y 2 +z 2 ,
so f = u1/2 . From the chain rule we have
1

1
u 2
u
1 1
f
=

= u( 2 1) 2x = xu 2 .
x
u
x
2
Therefore the second derivative is (from the product and chain rules):
1

1
3

u 2
u
2f
12
=
(x)

u
+
x

= u 2 x2 u 2 .
x2
x
u
x
Since f and u are symmetric in x, y and z we have

2f
y 2

= u 2 y 2 u 2

1
3
2f
= u 2 z 2 u 2 .
z 2

and

## Adding these results and using x2 + y 2 + z 2 = u yields

 1
  1
  1

3
3
3
2 f =
u 2 x2 u 2 + u 2 y 2 u 2 + u 2 z 2 u 2
=

## Click on the green square to return

3u 2 (x2 + y 2 + z 2 )u 2 = 2u 2 = p

x2

.
+ y2 + z2 

Solutions to Exercises

21
1

## Exercise 2(d) To find the Laplacian of f = (x2 + y 2 + z 2 ) 2 , we

again define u = x2 + y 2 + z 2 . From the chain rule
1

3
1
f
u 2
u
1
=

= u( 2 1) 2x = xu 2 .
x
u
x
2
Thus the second order derivative is:
3

3
5

2f
u 2
u
32
=

(x)

= u 2 + 3x2 u 2 .
x2
x
u
x
Due to the symmetry under interchange of x, y and z :
3
5
2f
2f
32
2 52
=
u
= u 2 + 3z 2 u 2 .
+
3y
u
,
2
2
y
z
Therefore we find that the Laplacian of f vanishes:

 
 

3
5
5
5
3
3
2 f = u 2 + 3x2 u 2 + u 2 + y 2 u 2 + u 2 + 3z 2 u 2
3

= 3u 2 + 3(x2 + y 2 + z 2 )u 2 = 3u 2 + 3u 2 = 0 .
Click on the green square to return

Solutions to Exercises

22

Exercise 3(a)
If the gradient of the scalar function f is f = 2xzi + x2 k, then the
Laplacian of f is given by the divergence of this vector
2 f = div (f ) .
Therefore the Laplacian of f is
2 f

=
=
=
=


div 2xzi + x2 k

2
(2xz) +
(0) +
(x )
x
y
z
2z + 0 + 0
2z .

## Click on the green square to return



Solutions to Exercises

23

Exercise 3(b)
If a scalar field f has gradient f =

x
x
1
i 2 j 2 k , its Laplacian
yz
y z
yz

## is given by the divergence

2 f = div (f ) .
Using this formula we can find 2 f as follows


x
1
x
2
f = div
i 2 j 2k
yz
y z
yz

 




x
=
+
2
+
2
x yz
y
y z
z
yz
x
x
= (0) (2) 3 (2) 3
y z
yz
y2 + z2
= 2x 3 3 .
y z
Click on the green square to return


Solutions to Exercises

24

Exercise 3(c)
As above if the gradient of f is
f = ez i + yj + xez k
its Laplacian is the scalar divergence of the vector f :
2 f = div (f ) .
Therefore
2 f

z

(e ) +
(y) +
(xez )
=
x
y
z
= (0) + 1 + xez
= 1 + xez .
=

## Click on the green square to return

Solutions to Exercises

25

Exercise 3(d)
1
1
1
If f = i + j + k , then the Laplacian of f is the divergence of
x
y
z
the gradient of f :
2 f = div (f ) .
Therefore


1
1
1
2
f = div
i+ j+ k
x
y
z
 
 
 

1
1
1
=
+
+
x x
y y
z z
1
1
1
= 2 2 2.
x
y
z
This may also be written as follows
2 f =

x2 y 2 + z 2 x2 + y 2 z 2
.
x2 y 2 z 2

## Click on the green square to return

Solutions to Exercises

26

Exercise 4(a)
To find the Laplacian of f = (2x 5y + z)(x 3y + z), we use
2 (uv) = (2 u)v + u2 v + 2(u) (v)
with u = 2x 5y + z and v = x 3y + z. This implies
u
v

= 2i 5j + k
= i 3j + k

and so
2 u = 2 v = 0
The above rule therefore gives:
2 f = 2u v

= 0 + 0 + 2(2i 5j + k) (i 3j + k)
= 2(2 + 15 + 1)
= 36 .

## Click on the green square to return



Solutions to Exercises

27

Exercise 4(b)
To find the Laplacian of f = (x2 y)(x + z), we use
2 (uv) = (2 u)v + u2 v + 2(u) (v)
with u = x2 y and v = x + z. This implies
u
v
and so
2 u = 2xi =

= 2xi j
= i+k
(2x)
=2
x

and 2 v = 0

## The above rule therefore gives:

2 f

=
=
=

2(x + z) + 0 + 2(2i j) (i + k)
2(x + z) + 2(2)
2(x + z + 2) .

## Click on the green square to return

Solutions to Exercises

28

Exercise 4(c)
To find the Laplacian of f = (y z)(x2 + y 2 + z 2 ), we use
2 (uv) = (2 u)v + u2 v + 2(u) (v)
with u = y z and v = x2 + y 2 + z 2 . This implies
u = j k

and 2 u = 0

while
v
2 u

= 2+2+2=6

2 f

= 6 + 2(0 + 2 2)
= 6.

## Click on the green square to return

Solutions to Exercises

29

p
Exercise 4(d) To find the Laplacian of f = x x2 + y 2 + z 2 , we
use
2 (uv) = (2 u)v + u2 v + 2(u) (v)
p
with u = x and v = x2 + y 2 + z 2 . Therefore u = i and 2 u = 0 .
p
In Exercise 2(c) we saw 2 v = 2/ x2 + y 2 + z 2 . To find v use
2
1
3
the chain rule:
(x + y 2 + z 2 ) 2 = 2x ( 21 ) (x2 + y 2 + z 2 ) 2
x
and similarly for the other partial derivatives. Thus
1
v =
3 (xi + yj + zk)
2
(x + y 2 + z 2 ) 2
The above rule therefore gives:
2
1
2 f = 0 + x p
+ 2i
3 (xi + yj + zk)
2
2
2
2
(x + y 2 + z 2 ) 2
x +y +z
2x2
2x

= p
3 .
(x2 + y 2 + z 2 ) 2
x2 + y 2 + z 2
Click on the green square to return


Solutions to Quizzes

30

Solutions to Quizzes
Solution to Quiz: The first and the second order partial derivatives
1
of f = rn , r = (x2 + y 2 + z 2 ) 2 with respect to the variable x read:
n
f
r
r
x
x
=

= nrn1 = n n+2 .
x
r
x
r
r


2f
1 x
r

1
=
n

xn

x2
rn+2 x
r rn+2
x
x2
1
= n n+2 + n(n + 2) n+4 .
r
r
Due to the symmetry under interchange of x, y and z we have also
2f
1
y2
2f
1
z2
=
n
+
n(n
+
2)
,
=
n
+
n(n
+
2)
.
y 2
rn+2
rn+4
z 2
rn+2
rn+4
Adding these second order derivatives yields the Laplacian:
2 f =

3n
rn+2

+ n(n + 2)

x2 + y 2 + z 2
n(n 1)
=
.
rn+4
rn+2
End Quiz

Solutions to Quizzes

31

Solution to Quiz:
The Laplacian of the vector field F = x3 yi + ln(z)j + ln(xy)k is a
vector 2 F whose i , j components are correspondingly
2 (x3 y)

2 (ln(z))

2 3
2
2
(x y) + 2 (x3 y) + 2 (x3 y) = 6xy ,
2
x
y
z
 
1
2
1
(ln(z)) =
= 2,
2
z
z z
z

## while the k component is

2 (ln(xy))

= 2 (ln(x) + ln(y)) =

1
1
x2 + y 2

.
x2
y2
x2 y 2

## So the Laplacian of F is:

2 F = 6xyi

1
x2 + y 2
j

k.
z2
x2 y 2
End Quiz

Solutions to Quizzes

32

Solution to Quiz:
The Laplacian of the vector field F = 3x2 zi sin(y)j + ln(2x3 )k is
a vector 2 F whose i , j and k components are correspondingly

2
2
2
(3x2 z) + 2 (3x2 z) + 2 (3x2 z) = 6z ,
2 3x2 z
=
2
x
y
z
2

## 2 ( sin(y)) = 2 (sin(y)) = ( cos(y)) = 2 sin(y) ,

y
y
2
2

1

(ln(2x3 )) =
(ln(2) + 3 ln(x))) = 3 2 ,
2 ln(2x3 ) =
2
2
x
x
x
Therefore the Laplacian of F is
1
2 F = 6zi + 2 sin(y)j 3 2 k ,
x
and evaluating it at the point (1, 2, 1) we get
2 F = 6i + 2 sin(2)j 3k = 6i 3k .
End Quiz

Solutions to Quizzes

33

Solution to Quiz:
The Laplacian of F = ln(y)i+z 2 j sin(2x)k at (1, 1, ) is the vector
whose i, j and k components are in turn given by:
1
2 ln(y) 2 ln(y) 2 ln(y)
+
+
= 0 2 + 0,
2
2
2
x
y
z
y
2 2
2 2
2 2

z
2 z 2 =
+
+
= 0 + 0 + 2,
x2
y 2
z 2
2 sin(2x) 2 sin(2x) 2 sin(2x)
2 sin(2x) =
+
+
x2
y 2
z 2
2
= 4 sin(2x) + 0 + 0 ,
2 ln(y)

Therefore we have
2 F =

1
i + 2j 4 2 sin(2x)k
y2

End Quiz